Transverse effect of Haas and Hyrax appliances on the upper dental arch in patients with unilateral complete cleft lip and palate: A comparative study - Anna Júlia de Oliveira Façanha; Tulio Silva Lara; Daniela Gamba Garib; Omar Gabriel da Silva Filho (Dental Press Editora, 2014)
Objective: The aim of the present study was to evaluate the transverse effect of rapid maxillary expansion in patients with unilateral complete cleft lip and palate while comparing the Haas and Hyrax appliances. Methods: The sample consisted of 48 patients divided into two groups: Group I - 25 patients treated with modified Haas appliance (mean age: 10 years 8 months); and Group II - 23 patients treated with Hyrax appliance (mean age: 10 years 6 months). Casts were taken during pre-expansion and after removal of the appliance at the end of the retention period. The models were scanned with the aid of the 3 Shape R700 3D scanner. Initial and final transverse distances were measured at cusp tips and cervical-palatal points of maxillary teeth by using the Ortho Analyzer(tm) 3D software. Results: The mean expansion obtained between cusp tips and cervical-palatal points for inter-canine width was 4.80 mm and 4.35 mm with the Haas appliance and 5.91 mm and 5.91 mm with the Hyrax appliance. As for first premolars or first deciduous molars, the values obtained were 6.46 mm and 5.90 mm in the Haas group and 7.11 mm and 6.65 mm in the Hyrax group. With regard to first molars, values were 6.11 mm and 5.24 mm in the Haas group and 7.55 mm and 6.31 mm in the Hyrax group. Conclusion: Rapid maxillary expansion significantly increased the transverse dimensions of the upper dental arch in patients with cleft palate, with no significant differences between the Hass and Hyrax expanders.